ANALISIS FRAMING KOMUNIKASI PEMERINTAH DALAM PROGRAM PENURUNAN PREVALENSI STUNTING DI KABUPATEN ACEH BARAT - Amanda, Shinta Riski; Nuri, Nuri; Alfizra, Luthfi (Istek Widuri Jakarta, 2023)
Stunting is a global health problem that is still a serious concern for many countries, including Indonesia. Stunting occurs due to a lack of adequate nutrition in children, causing stunted body growth. Stunting can have long-term impacts on children's health and development, as well as impact quality of life and future productivity. The purpose of this research is to see how the media frames how the government communicates in the stunting program in West Aceh district. This study uses a descriptive qualitative research method with a framing approach, namely a method to find out how the media tells the story (storytelling) of an event. By using this method, data analysis is carried out by collecting news about government programs in accelerating the reduction of stunting and then seeing how the news is framing the news. The results and discussion are honestly presented by the systematics of the composition of the news published with the framing framework of Robert N, namely Define Problem, Diagnose Cause, Make Moral Judgment (Make Personal Decisions) and Treatment Recommendation (Problem Solving). There are various views in the news that frame the same issue, as happened in the news on stunting in West Aceh District. Framing is the process of selecting and emphasizing several aspects of an event or a particular issue so as to influence people's views and attitudes towards the issue. West Aceh has launched a stunting program, namely Healthy Kitchens Overcome Stunting (DASHAT) in 48 quality family villages, where this is made to reduce stunting which often occurs in Indonesia, especially in West Aceh District.